The Effect Of Financial Distress And Audit Report Lag On The Integrity Of Financial Statements (A Study on Banking Companies Listed on the Indonesia Stock Exchange During the 2020–2025 Period) - NH Salsabiela; Nur Zeina Maya Sari; Ayi Astuti (Business Management, 2026)
This study aims to examine the effect of financial distress and audit report lag on the integrity of financial statements in banking sector companies listed on the Indonesia Stock Exchange during the 2020–2025 period. The integrity of financial statements is an important aspect in presenting financial information that is reliable, relevant, and trustworthy for users of financial statements. Financial distress conditions and audit report lag are assumed to influence the quality and integrity of a company’s financial statements. This study employed descriptive and verificative methods with a quantitative approach. The sampling technique used purposive sampling, resulting in a sample of banking companies that met the research criteria. The data used were secondary data in the form of financial statements and annual reports obtained from the official website of the Indonesia Stock Exchange and related company websites. The data analysis method used multiple linear regression analysis with the assistance of SPSS software. The results of the study indicate that financial distress has no significant effect on the integrity of financial statements. This finding suggests that a company’s financial difficulties do not directly affect the integrity of financial statements because companies are still required to prepare financial statements in accordance with accounting standards and regulatory provisions. Furthermore, audit report lag also has no significant effect on the integrity of financial statements. The length of the audit process does not necessarily reflect low integrity of financial statements, but may indicate the auditor’s level of prudence in examining the company’s financial statements. Therefore, the integrity of financial statements in the banking sector is more influenced by regulatory compliance, the quality of internal supervision, and the implementation of good corporate governance.